Red 2 [videorecording (DVD)] - Willis, Bruce, 1955-; Malkovich, John; Parker, Mary-Louise; Zeta-Jones, Catherine, 1969-; Hopkins, Anthony, 1937-; Mirren, Helen (di Bonaventura Pictures, 2013)
Retired black-ops CIA agent Frank Moses rejoins his unlikely team of elite operatives for a global quest to track down a missing portable nuclear device.